2011
DOI: 10.1212/wnl.0b013e3182309f91
|View full text |Cite
|
Sign up to set email alerts
|

Early stroke risk and ABCD2 score performance in tissue- vs time-defined TIA

Abstract: Objectives: Stroke risk immediately after TIA defined by time-based criteria is high, and prognostic scores (ABCD2 and ABCD3-I) have been developed to assist management. The American Stroke Association has proposed changing the criteria for the distinction between TIA and stroke from time-based to tissue-based. Research using these definitions is lacking. In a multicenter observational cohort study, we have investigated prognosis and performance of the ABCD2 score in TIA, subcategorized as tissue-positive or t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
110
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 147 publications
(122 citation statements)
references
References 38 publications
5
110
2
5
Order By: Relevance
“…Tables 24-26 show the risk of recurrent stroke stratified by the presence of brain infarction on imaging and dichotomised ABCD2 score (above and below 4). Data were derived from the systematic review conducted by Giles and colleagues in 2011, 210 who reported published and unpublished TIA data from 12 independent centres. Patients with ABCD2 score ≥ 4 and visible lesion on CT or DWI had a 7-day risk of stroke of 10.7%, compared with 1.9% in those without visible lesion; for patients with ABCD2 score of < 4 the risk of stroke was 2.3% and 0.2%, respectively.…”
Section: Abcd2 Score and Diffusion-weighted Imaging Or Computed Tomogmentioning
confidence: 99%
“…Tables 24-26 show the risk of recurrent stroke stratified by the presence of brain infarction on imaging and dichotomised ABCD2 score (above and below 4). Data were derived from the systematic review conducted by Giles and colleagues in 2011, 210 who reported published and unpublished TIA data from 12 independent centres. Patients with ABCD2 score ≥ 4 and visible lesion on CT or DWI had a 7-day risk of stroke of 10.7%, compared with 1.9% in those without visible lesion; for patients with ABCD2 score of < 4 the risk of stroke was 2.3% and 0.2%, respectively.…”
Section: Abcd2 Score and Diffusion-weighted Imaging Or Computed Tomogmentioning
confidence: 99%
“…[1][2][3] The presence and the volume of DWI lesions carry a negative prognostic value in this population. [4][5][6] The DWI-restricted lesions are thought to represent the irreversibly damaged ischemic core.…”
mentioning
confidence: 99%
“…2,14,15 Other studies demonstrated that TIA patients in low-risk (0-3 points), moderate-risk (4-5 points), high-risk groups (6-7 points) presented incidence of cerebral infarction of 3%, 31% and 3%, respectively (P<0.05) within 7 d. TIA patients with secondary to cerebral infarction within 7 d probability and linear correlation between ABCD2 score showed that high score indicates high incidence of cerebral infarction; ABCD2 score >6 displays highest incidence in patients, and risk of recurrence of cerebral infarction is seven times higher than that of other patients. 16,17 To date, numerous studies proved that efficiency of ABCD2 score for early prediction of cerebral infarction after TIA value is higher than that of ABCD score method, with recommendations of AHA/ASA for clinical evaluation of the prognosis of patients with TIA risk method. 2 In recent years, a growing number of studies have shown that ABCD2 score for prediction of stroke after TIA features more limitations because of lack of etiology assessment, making ABCD2 score prediction value questionable.…”
Section: Abcd2 Scorementioning
confidence: 99%